Antimicrobial activity of crude extract from antibiotic producing fungi - Norlaila, binti Deraman (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Fungi have been used for producing medically useful compound. Although there are a large number of fungi species, only a relative few have been found to produce antibiotics. Nowadays, the bacteria become resistance toward antibiotics because of overuse of the antibiotics in the treatment of bacterial infection. The objectives of this study are to determine antimicrobial activity of crude extracts from antibiotic producing fungi and to compare the effectiveness of antibacterial properties among four different crude extracts using three different assays. Evaluation on antimicrobial activity was done on crude extract using four different solvents and five different concentrations. The solvents involved in this research including hexane, dichloromethane (DCM), ethyl acetate, and methanol. The concentration used were 1.0 mg/µl, 0.5 mg/µl, 0.25 mg/µl,0.125 mg/µl and 0.0623 mg/µl. Antimicrobial activity of crude extracts was determined using different bacteria which are three Gram-negative bacteria, Escherichia coli, Salmonella typhi, Enterobacter aerogenes and one Gram-positive bacteria, Staphylococcus aureas. The disc diffusion assay, broth microdilution assay and direct bioautographic assay was the method used to determine antimicrobial activity using the crude extracts from the antibiotic producing fungi. All of the crude extracts showed different antimicrobial activity toward different bacteria. From the result hexane and ethyl acetate extracts showed active against Gram negative bacteria, E. aerogenes and Gram positive bacteria S. aureas.